Analisis Strategi Kepala Sekolah Meningkatkan Kemampuan Guru Membuat Alat Peraga dalam Kegiatan Pembelajaran - Nopa Wilyanita; Radhiyatul Fithri; Mulkiah Syah; Melvi Lesmana Alim Alim (Journal on Education, 2023)
Teaching aids are media made by teachers for students so they can quickly understand learning. The purpose of this research is to find out how the principal's strategy is to improve the teacher's ability to make visual aids in learning activities so that learning is of higher quality. The focus of this research is to increase teacher competence in making visual aids. This type of research is descriptive qualitative. Data collection techniques through observation, interviews, and documentation. The data analysis technique uses the Miles Huberman model, namely the stages of data collection, data editing, data presentation and drawing conclusions. The results of research conducted on the analysis of school principals in improving the ability of teachers to make teaching aids are providing motivation, a comfortable school environment, discipline, carrying out their duties well, inviting teachers to work together, providing brilliant ideas, providing tools to make teaching aids, giving gifts, and sanctions against teachers are generally successful in terms of the current state of schools that are already using visual aids for classroom learning. The implementation of the teacher must not stop being creative in making and using teaching aids for creative and innovative learning.